DAMPAK KESEHATAN AKIBAT KEKERASAN TERHADAP TENAGA KERJA INDONESIA - Helfi Agustin (Faculty of Public Health, Andalas University, 2008)
Indonesian government has determined a policy of employment placement as national program. With the raising number of Indonesian migrant workers, also of problem about it. The research is qualitative research and data were taken by indepth interview methode. Aim’s to know what the health impacts resulting from violations of Indonesian migrant workers. It is used tematic analysis. The research was held in West Sumatera province, Jogjakarta, Jakarta, Banten in April –June 2006. As a result of the research found out that all of Indonesian Migrant Workers who left in young ages. All of the Indonesian migrant workers experience of abuses that impact to economic aspect, but women and Ilegal Indonesian migrant workers faced higher risk violation and undergo abuse with greater impact. Executive should have improve citizen awareness in the aim to prevent abuse through elliminate ilegal leaving by giving information to publict, and have political commitment to revise rules/diplomation which oriented to human right protection of Indonesian migrant workers. Indonesian Manpower Service Personnel is suggested to promoting and giving truth information for sale of job order. NGO could have improve citizen awareness about human right and fact that violation can be prevented.